A ten-year bibliometric study on mathematical ability - Gusteti, Meria Ultra; Musdi, Edwin; Dewata, Indang; Fauzan, Ahmad; Arnawa, I Made; Rasli, Amran Md. (International Journal of Evaluation and Research in Education (IJERE), 2025)
Mathematical ability is a crucial aspect of modern life as it influences various fields such as economics, technology, and science. This study, spanning 2014-2023, examines articles on mathematical ability in leading journals. Using the bibliometric methods, it includes article searches in Scopus and Google Scholar via Publish or Perish (PoP), classification for bibliometric analysis, metadata checks, and bibliometric analysis using VOSviewer. The research shows a consistent trend in publications on mathematical ability, with minimal fluctuations and significant citation patterns. High-citation articles underscore the field’s importance in knowledge advancement. Key terms are ‘ability’, ‘mathematical ability’, and ‘student’, indicating research focus areas. However, limited author collaboration suggests potential for increased interdisciplinary synergy and knowledge sharing. These findings highlight opportunities for enhancing cross-disciplinary collaborations and research networks. They offer insights for policymakers, educators, and researchers in understanding trends, developing effective learning strategies, and encouraging further research in mathematical ability. In summary, this bibliometric study provides a comprehensive overview of the significance of mathematical ability in research, emphasizing the need for collaborative, innovative educational and research practices. It underscores the importance of further research to deepen understanding and application of mathematical ability, promoting an integrative approach in this essential field.